Traitors and the Art of Self-Censoring - Sanathanan, T. (My University, 2022)
After the wining the civil war in 2009, the president of Sri Lanka announced that hereafter there would be no majorities and minorities in Sri Lanka but patriots and traitors. This re-labelling while allowing the age old inequalities to continue, marks all the voices of dissent as non-patriotic. In the post-independence politics of Sri Lanka, competing political parties and armed groups constantly use the word traitor to single out individuals and groups who have differences in opinion, ideology and vision. Dissent has been seen as a threat. On the other hand the nation-building project in Sri Lanka constantly produced its ›Other‹ along the line of binaries such as Aryan–Dravidian, native–invader, Sinhalese– Tamils, majority–minority and South–North.